A case-practice-theory-based method of implementing energy management in a manufacturing factory. Issue 7 (3rd August 2021) - Ma, Shuaiyin; Zhang, Yingfeng; Ren, Shan; Yang, Haidong; Zhu, Zhenfei
ABSTRACT: Energy management effectively reduces energy consumption, improves material utilisation, minimises emissions and maximises product output during manufacturing. Thus, enterprises are implementing an energy management strategy and improving sustainable competitive advantage. With the rapid development of the Internet of Things, Cyber-Physical Systems and Big Data, sustainable smart manufacturing provides a new strategy for energy management by applying advanced information technologies. In practice, energy management is an enormous opportunity given the lack of such implementation. This paper presents a case-practice-theory-based (CPTB) method of implementing energy management in the manufacturing factory for energy saving and emission reduction. The closed-loop structure of the proposed CPTB method is designed and implemented. Then, an application of six hot-blast stoves in moulding workshops of a partner company is presented to demonstrate the proposed method. Results showed that after employing the method, the unit energy consumption of production reduced by approximately 3%, and saved energy costs reached 4%. Finally, a discussion analyses the managerial implications for ceramic and other energy-intensive manufacturing industries.